Implementation of Deep Learning Through the Integration of Digital Interactive Boards - Adelia Putri; Azi Matur Rahmi (Sekolah Tinggi Agama Islam YDI Lubuk Sikaping, 2026)
This study examines the implementation of deep learning through the integration of digital interactive boards at TKIT Husnul Khotimah, Cikarang District, West Java. The use of interactive screen-based technology in early childhood education institutions is growing in line with the demands of the digital era, which encourages more innovative, interactive, and child-centered learning. The study used a descriptive qualitative approach with a case study method. Data were obtained through observation, in-depth interviews, and documentation involving the principal, class teachers, and students aged 4–6 years in the 2025/2026 academic year. The results showed that the implementation of digital interactive boards had a positive impact on the quality of the learning process. This media was able to create more interesting, interactive, and child-centered learning through the use of visual materials, audio, educational videos, and various interactive activities directly on the screen. Students showed increased attention, learning motivation, active participation, creativity, and conceptual understanding. In addition, teachers were helped in delivering material more effectively and variedly. Although there are still obstacles in the form of limited mastery of technology by some teachers and less than optimal use of device features, overall, the implementation of digital interactive boards has proven effective in supporting in-depth learning and improving the quality of early childhood education